Emerging Therapies to Prevent Skeletal Morbidity in Men With Prostate Cancer - Saylor, Philip J. (American Society of Clinical Oncology, 2011)
Skeletal morbidity is a prominent burden to men with advanced prostate cancer throughout the natural history of the disease. Bone metastases can cause pain and greatly elevate the risk for fractures and other structural complications. Distinct from the problem of metastases, treatment-related osteoporosis and associated fragility fractures are potential complications of androgen-deprivation therapy. Bone-targeted therapies for prostate cancer have therefore been the focus of considerable research and drug development efforts. The osteoclast is a validated therapeutic target in the management of prostate cancer. Osteoclast inhibition with zoledronic acid (a bisphosphonate) or with denosumab (a monoclonal antibody to RANK ligand) reduces risk for skeletal events in men with castration-resistant prostate cancer metastatic to bone. Osteoclast inhibition with any of several bisphosphonates improves bone mineral density, a surrogate for osteoporotic fracture risk. Denosumab and toremifene (a selective estrogen receptor modulator) have each been shown to reduce osteoporotic fracture risk among men receiving androgen-deprivation therapy. Beta-emitting radiopharmaceuticals reduce pain due to metastatic disease. Investigations involving alpha-emitting radium-223, endothelin-A receptor antagonists atrasentan and zibotentan, proto-oncogene tyrosine-protein kinase (SRC) inhibitor dasatinib, and tyrosine kinase inhibitor cabozantinib (XL184) are ongoing in clinical trials and are also discussed.